Pesticide exposures and the risk of multiple myeloma in men: An analysis of the North American Pooled Project. Issue 8 (28th June 2016) - Presutti, Roseanna; Harris, Shelley A.; Kachuri, Linda; Spinelli, John J.; Pahwa, Manisha; Blair, Aaron; Zahm, Shelia Hoar; Cantor, Kenneth P.; Weisenburger, Dennis D.; Pahwa, Punam; McLaughlin, John R.; Dosman, James A.; et al.
Abstract : Multiple myeloma (MM) has been consistently linked with agricultural activities, including farming and pesticide exposures. Three case‐control studies in the United States and Canada were pooled to create the North American Pooled Project (NAPP) to investigate associations between pesticide use and haematological cancer risk. This analysis used data from 547 MM cases and 2700 controls. Pesticide use was evaluated as follows: ever/never use; duration of use (years); and cumulative lifetime‐days (LD) (days/year handled × years of use). Odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using logistic regression adjusted for age, province/state of residence, use of proxy respondents and selected medical conditions. Increased MM risk was observed for ever use of carbaryl (OR = 2.02, 95% CI = 1.28–3.21), captan (OR = 1.98, 95% CI = 1.04–3.77) and DDT (OR = 1.44, 95% CI = 1.05–1.97). Using the Canadian subset of NAPP data, we observed a more than threefold increase in MM risk (OR = 3.18, 95% CI = 1.40–7.23) for ≤10 cumulative LD of carbaryl use. The association was attenuated but remained significant for >10 LD of carbaryl use (OR = 2.44; 95% CI = 1.05–5.64; p trend  = 0.01). For captan, ≤17.5 LD of exposure was also associated with a more than threefold increase in risk (OR = 3.52, 95% CI = 1.32–9.34), but this association was attenuated in the highest exposure category of >17.5 LD (OR = 2.29, 95% CI = 0.81–6.43; p trend  = 0.01). An increasing trend ( p trend  = 0.04) was observed for LD of DDT use (LD > 22; OR = 1.92, 95% CI = 0.95–3.88). In this large North American study of MM and pesticide use, we observed significant increases in MM risk for use of carbaryl, captan and DDT. Abstract : What's new? Multiple myeloma, a cancer of terminally differentiated B cells, is more frequent in farmers compared to the general population but precise risk estimates remain unclear. Here, the authors pooled case‐control studies from the United States and Canada to form the North American Pooled Project focused on agricultural and pesticide exposures and haematological cancers. They observed significant increases in multiple myeloma risk for self‐reported use of pesticides such as carbaryl, captan and DDT, providing more refined risk estimates of exposure.